Toxicity and Protective Effect of Phenolic‐Enriched Ethylacetate Fraction of Ocimum gratissimum (Linn.) Leaf against Acute Inflammation and Oxidative Stress in Rats. Issue 3 (June 2017) - Ajayi, Abayomi M.; Umukoro, Solomon; Ben‐Azu, Benneth; Adzu, Bulus; Ademowo, Olusegun G.
ABSTRACT: Preclinical Research Ocimum gratissimum L. leaves have attracted considerable attention from researchers because of their medicinal value that include anti‐inflammatory, analgesic, antimicrobial, and antioxidant activities. In the present study, the toxicity and the protective effect of phenolic extract of O. gratissimum leaf (EAFO g ) against acute inflammation and oxidative stress in rats was assessed. EAFOg, enriched in phenols had no cytotoxic effect against CHO‐k1 cells, and no lethality against brine shrimp eggs or mice at a dose of 2000 mg/kg. EAFOg (50 and 100 mg/kg) reduced paw edema by 47% and 61%, compared to 29% with the COX‐2 inhibitor, SC58125 (1 mg/kg) and 81% with indomethacin (5 mg/kg), respectively. In the rat carrageenan‐induced air pouch model, EAFO g reduced exudate volume, leucocyte count, nitrite, TNF‐α, and myeloperoxidase activity. EAFO g also protected against carrageenan‐induced lipid peroxidation and glutathione depletion. These results provide evidence of the protective effects of EAFO g against acute inflammation and oxidative stress in rats. Drug Dev Res 78 : 135‐145, 2017. © 2017 Wiley Periodicals, Inc.